Supranuclear gaze palsy and opsoclonus after Diazinon poisoning. Issue 5 (1st May 2003) - Liang, T-W; Balcer, L J; Solomon, D; Messé, S R; Galetta, S L
Abstract : A 52 year old man developed a supranuclear gaze palsy and opsoclonus after Diazinon poisoning. The diagnosis was confirmed by low plasma and red blood cell cholinesterase activity and urine mass spectroscopy. Saccadic control may be mediated in part by acetylcholine. Opsoclonus in the setting of organophosphate intoxication may occur as a result of cholinergic excess which overactivates the fastigial nuclei.